The breeding biology of the Coal Tit Periparus ater in South Central Sweden - Schölin, Karl Gustav; Källander, Hans (Ornis Svecica, 2013)
In a nestbox study started in 1948 and still ongoing, the number of breeding Coal Tits Periparus ater was always low. Here we present data on time of egg laying and its advancement during the last three decades, clutch size, fledging success and proportion of second broods. Laying dates varied between 18 April and 10 May, with an overall mean of 5 May, and advanced by 0.36 days per year during the second half of the study. Mean clutch size was 8.55 (first clutches). A mean of 7.25 young fledged (all first broods) or 7.78 (failed first broods excluded). Second broods (12.6%) were often not checked but seven clutches had a mean size of 7.23 eggs and fledged 6.71 young.